Efecto de un calentamiento con estiramientos estáticos y dinámicos sobre el salto horizontal y la capacidad para repetir esprint con cambio de dirección - Sanchez-Sanchez, J.; Rodriguez-Fernandez, A.; Villa-Vicente, J. G.; Petisco-Rodriguez, C.; Ramirez-Campillo, R.; Gonzalo-Skok, O. (Revista Internacional de Ciencias del Deporte, 2017)
The purpose of this study was to compare the effect of three different warm-ups (low intensity aerobic warm-up, static stretching and dynamic stretching) on the horizontal jump and repeated sprint ability with changes of direction. Seventeen players of team sports whose age was 20.8±1.1 years old performed three types of warm up (10 minutes): aerobic exercise without stretching (WU), with static stretching (WUSS) and with dynamic stretching (WUDS). The acute effect of each warming over performance was studied in a test of horizontal jump (HJ) and repeat sprint test with change of direction (RSCD). No significant differences were obtained (p>0.05) in any of the variables studied according to the warming developed. The effect size (ES) indicated that probably RSCDbest was more sensitive to WU than WUDS (ES: 0.52) and WUDS (ES: 0.44). The limited effect of static stretching on SH and RSCOD may be due to the dose, intensity and recovery time. The dynamic stretching did not improve performance in HJ and RSCD.